Numerical Solution of Electrostatic Potential Distribution on a Unit Circular Disc Using Possion Equation - Basnet, Ganesh Bahadur (Nepal Journal of Mathematical Sciences, 2023)
In this paper, the two-dimensional electrostatic potential distribution problem has been solved numerically using the finite difference approach using Poisson’s equation in polar coordinates with Dirichlet’s boundary condition inside a unit circular disc. We also use Gauss elimination method to solve numbers of linear equations to obtain solutions of unknowns at each grid point. The numerical solution to the same problem is contrasted with the analytic solution. Finally, we examine the absolute errors throughout a range of iterations to evaluate the accuracy of the schemes.